ANALISIS PENGARUH PSIKOLOGIS KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO (STUDI KASUS PADA MAHASISWA STIE BIMA) - Apriyadi Bimantara dan Ita Purnama (JOURNAL SCIENTIFIC OF MANDALIKA (JSM), 2021)
This study aims to determine the psychological influence of consumers on purchasing decisions for Oppo smartphones (a case study on students of stie bima). This research is an associative research which shows the influence between two or more variables. The sample in this study were 96 people. Data collection techniques used are observation, documentation and questionnaires. The data analysis technique used is multiple linear regression test, validity and reliability test, determination test, t test and F test. The results of the study show that this study states that (1) motivation partially does not affect the purchasing decision of Oppo smartphone (2) perception of quality partially has no effect on purchasing decisions for smartphones oppo (3) learning partially affects purchasing decisions for smartphones oppo (4) partial attitudes have no effect on purchasing decisions for smartphones oppo (5) simultaneously or simultaneously consumer psychology, motivation, perceived quality, learning and attitudes affect the purchasing decisions of smartphones oppo. on the purchasing decisions of smartphones oppo